THE ROLE OF ASSISTIVE TECHNOLOGIES IN OLIGOPHRENOPEDAGOGY - Alijonova , Dilorom (WORLD INTERNATIONAL CONFERENCE ON SCIENCE, TECHNOLOGY AND EDUCATION, 2026)
This article discusses the use of assistive technologies in oligophrenopedagogy, their importance in the education of children with intellectual disabilities, and their role in improving the effectiveness of the educational process. It also analyzes the possibilities of implementing an individualized approach through modern technological tools.